Detection of Alphitobius diaperinus by Real-Time Polymerase Chain Reaction With a Single-Copy Gene Target - Marien, Aline; Sedefoglu, Hamza; Dubois, Benjamin; Maljean, Julien; Francis, Frédéric; Berben, Gilbert; Guillet, Stéphanie; Morin, Jean-François; Fumière, Olivier; Debode, Frédéric (Frontiers in Veterinary Science, 2022)
Use of edible insects as an alternative source of proteins in food and feed is increasing. These last years, numerous companies in Europe have started producing insects for food and feed purposes. In the European Union, the use of edible insects for human consumption falls within Regulation (EU) No. 2015/2283 on novel foods. For feed, Commission Regulation (EU) 2017/893 authorizes seven insect species as processed animal proteins for aquaculture. Methods of authentication are required to check the conformity of the products. In this study, we propose a real-time PCR method for the specific detection of the lesser mealworm (Alphitobius diaperinus), one of the species included in the shortlist of authorized insects. The selected target is the cadherin gene with a single-copy (per haploid genome) illustrated by our experimental evidence. The PCR test amplified a 134 bp fragment of the cadherin gene. The qualitative method was assessed towards several performance criteria. Specificity was checked against 54 insect species next to other animal and plant species. The sensitivity, efficiency, robustness and transferability of the PCR assay were also successfully tested. Finally, the applicability of the test was assessed on real-life processed samples (industrial meals) of A. diaperinus. The study also showed that there seems to be a huge confusion on the correct labelling of the marketed mealworms. We did not succeed to get A. laevigatus samples. They all appeared to belong to the A. diaperinus taxon.